Técnica de la lectura en la comprensión lectora en el proceso de enseñanza online generado por la pandemia covid 19 en el tiempo de emergencia sanitaria reflexionando desde la carrera de educación básica de la FCJSE UTB, cantón Babahoyo Provincia Los Ríos - Baños Párraga, Natacha del Carmen (2020)
The objective of this case study was to analyze the reading techniques in reading comprehension in the online teaching process generated by the covid-19 pandemic in the time of health emergency, reflecting on the basic education career of the FCJSE UTB, canton Babahoyo province Los Ríos. A qualitative research methodology was used, field modality, the interview was used to obtain data, messages were used through the cell phone to be able to carry out the interviews with teachers and students. Reading comprehension in the training of university students is considered a fundamental element for their professional development, however the research showed that the level of reading comprehension of students when carrying out reading activities is low, students do not assume their responsibility and participation in their own learning, teachers apply reading techniques when working from virtual classrooms, but they do not generate motivation in the student, so that they learn to interpret and analyze, the results indicate the reading deficiency of the students of the education career basic, virtual classes generate dissatisfaction on the part of students, so they suggest that teachers use reading techniques that favor learning, without forgetting that they require knowing learning strategies, in addition to being motivated to be able to learn in a meaningful way, online modality harms students' school performance heck.